Toobacco Education School in Risk Groups and Indixes for Evaluation - Llopiz Guerra, Karel (2020)
Smoking is one of the scourges suffered by contemporary society, and children are not exempt from this risk, a fact that becomes a starting point for conducting this research based on the criteria of health education and particularly, in the smoking education. The objective of the research seeks to analyze the knowledge and behaviors obtained by a selected group of fourth-grade schoolchildren in risk groups before smoking, allowing the changes to be measured using the weighted indices for their evaluation. Different methods and instruments of empirical level were applied such as document analysis, observation, analysis of the products of the activity, the pedagogical test in the initial and final stage, where the sources of information were organized and systematized according to the object study. The analysis and discussion of the results in the initial and final stage was expressed through the control and quantitative evaluation of the variables in order withthe purpose of guaranteeing the validity of the results, in addition the qualitative criteria achieved on smoking control were analyzed.